The Forgotten Ureteral Stent in Children: From Diagnosis to Treatment - Sancaktutar, Ahmet Ali; ADANUR, Şenol; Resorlu, Berkan; Tepeler, Abdulkadir; Ziypak, Tevfik; Soylemez, Haluk; Atar, Murat; BOZKURT, YAŞAR; PENBEGÜL, NECMETTİN; TÜFEK, ADNAN; Yavuz, Sevgi (My University, 2013)
Purpose: We conducted a multicenter pediatric study of ureteral stents unintentionally left in situ.